Predicting Clinical Pregnancy Rates in IVF-ET Using Transvaginal 3D Ultrasound and Serum Hormone Levels - Ling Lan; DanYang; XinTan; Yu Kang (Journal of the Pakistan Medical Association, 2025)
Objective:To investigate the predictive value of transvaginal three-dimensional ultrasound combined with serum oestrogen and progesterone levels in enhancing the clinical pregnancy rate of in vitro fertilization-embryo transfer. Method: The study was conducted at the Reproductive and Women-Children Hospital, Chengdu University of Traditional Chinese Medicine, Chengdu, China, from September 2020 to March 2021, and comprised patients undergoing in vitro fertilization-embryo transfer with frozen-thawed embryo cycles. The day before embryo implantation, endometrial thickness and sub-endometrial blood flow parameters were measured using two-dimensional ultrasound and then converted to three-dimensional ultrasound mode to assess endometrial volume and sub-endometrial vascularisation parameters. Serum estradiol and progesterone levels were also measured on the day of transplantation. The subjects were categorised into pregnancy and non-pregnancy groups based on their outcomes. The correlation of two-dimensional and three-dimensional ultrasound parameters was compared alongside serum estradiol and progesterone levels with respect to clinical pregnancy outcomes. Data was analysed using SPSS 22. Results: Of the 100 women with mean age 32.8±8.3 years (range: 22-44 years), 56(56%) were in the clinical pregnancy group and 44(44%) were in the non-pregnancy group. There was no significant differences in endometrial thickness or twodimensional ultrasound sub-endometrial blood flow parameters between the groups (p>0.05). In contrast, endometrial volume and three-dimensional sub-endometrial vascularisation indices were significantly higher in the pregnancy group (p<0.05). Combining endometrial volume with serum estradiol levels yielded a predictive accuracy with area under the curve 0.735, sensitivity 77.3% and specificity 90.7%. Conclusion:Transvaginal three-dimensional ultrasound-derived endometrial volume and sub-endometrial vascularisation parameters, combined with serum estradiol levels, could significantly improve the prediction of clinical pregnancy success in cases of in vitro fertilization-embryo transfer. Keywords: Transvaginal three-dimensional ultrasound, Oestrogen level, Endometrial receptivity, In vitro fertilizationembryo transfer.